The Great Transition: mexican society in the era of oil depletion - Peniche Camps, Salvador (2020)
The paper explains the challenges that Mexico faces given the new context of oil depletion. We argue that, for the Mexican government, it is imperative to move to a new model that will help the economy face the great energy transition of the coming years. We conclude that in the new administration there is no realistic assessment of the prospects for the economy in the described context and that the proposed development scheme fails to weigh the role and limitations that characterize oil extraction in the current era. For the current and future governments there is no alternative other than to adjust the economic, financial, social and environmental perspectives of development to a scenario of expensive and scarce oil.